Pengawasan Pajak dalam Administrasi Perpajakan dengan Memanfaatkan Teknologi Informasi (Studi Pada Kantor Pelayanan Pajak Pratama Malang Selatan) - Haryo Seno Widiputra (Jurnal Administrasi Publik, 2014)
Abstract: The Tax Supervision in the Administration of Taxation by Making Use of Technology Information (Studies on Small Tax Office Malang Selatan ). Supervision is required because the community tendsÂ  to carry out their obligations to pay taxes voluntarily and is true. Based on the development of information technology and the increasingly rapid variety improvement in the bureaucracy continues to do, one of which carried the Directorate General of taxes. The results of this research are the supervision in the administration of taxation by making use of information technology has been going well. The Directorate-General of Taxes in designing a system or application either the tax Directorate General information systems (SIDJP) and approweb who used to oversee the Taxpayer's easy in usage and errors that can be identified as well. In the implementation of surveillance against the Taxpayer in terms of the information technology systems of existing barriers is likely to the slowness of the system at the time of its use, as well as the lack of a representative number of accounts still overseeing Taxpayers. While the obstacles in exercising direct supervision by visiting the tax payers they tend to avoid Taxpayers inspections conducted by tax officials. This need for more scrutiny of actions as well. Keywords: supervision, tax, technology information Abstrak: Pengawasan Pajak Dalam Administrasi Perpajakan dengan Memanfaatkan Teknologi Informasi (Studi pada Kantor Pelayanan Pajak Pratama Malang Selatan). Pengawasan merupakan hal yang wajib dilakukan karena masyarakat cenderung cukup berat untuk melaksanakan kewajibannya membayar pajak secara sukarela dan benar. Berdasarkan perkembangan teknologi dan informasi yang semakin pesat berbagai perbaikan dalam birokrasi terus dilakukan yang salah satunya dilakukan Direktorat Jenderal Pajak. Hasil dari pengamatan bahwa Direktorat Jenderal Pajak dalam mendesain suatu sistem maupun aplikasi baik itu SIDJP maupun approweb yang digunakan untuk mengawasi Wajib Pajak mudah dalam penggunaannya dan kesalahan yang ada dapat teridentifikasi dengan baik. Pelaksanaan pengawasan terhadap Wajib Pajak dari segi sistem teknologi informasi hambatan yang ada adalah cenderung lambatnya sistem pada saat penggunaannya, serta masih kurangnya jumlah account representative (AR) yang bertugas mengawasi Wajib Pajak. Serta dalam melaksanakan pengawasan langsung dengan mengunjungi Wajib Pajak (visit) tersebut cenderung Wajib Pajak menghindari adanya inspeksi yang dilakukan oleh pegawai pajak, sehingga dalam hal ini perlu adanya tindakan pengawasan yang lebih. Â  Kata kunci: pengawasan, pajak, teknologi informasiÂ